Stylistic Devices of Preach Used by Mama Dedeh in Program “Mama dan Aa Beraksi” in Indosiar - Anita Anita; Hermawati Syarif; Delvi Wahyuni (English Language and Literature, 2018)
This research describes about types of lexical and syntactical stylistic devices found in Mama Dedeh’s preaches in program “Mama dan Aa” in Indosiar. The source of data is transcript from eight videos Mama Dedeh in month January-June 2016 about the vice. From the analysis, Mama Dedeh’s preach uses seven types of lexical stylistic devices, those are interjection, simile, proverb, epigram, oxymoron, metaphor, and quotation and also uses eight types of syntactical stylistic devices, those are inversion, chiasmus, parallelism, repetition, climax, asyndenton, question in narrative and rhetorical question. There are 40 data of lexical stylistic devices found in this research and the most dominant is interjection (21 data) followed by quotation (11), oxymoron (2), simile (2), metaphor (1), proverb (1), and epigram (1). Then, syntactical stylistic devices found in Mama Dedeh’s preach has 76 data and the most dominant is question in narrative (31), followed by repetition (15), rhetorical question (11), parallelism (8), inversion and asyndenton has (4), chiasmus (2), and climax (1). So the most dominant of lexical stylistic device found in Mama Dedeh’s preach is interjection and the most dominant of syntactical stylistic devices is question in narrative.